Application of Ultrasound as Clean Technology for Extraction of Specialized Metabolites From Stinging Nettle (Urtica dioica L.) - Šic Žlabur, Jana; Radman, Sanja; Opačić, Nevena; Rašić, Anamaria; Dujmović, Mia; Brnčić, Mladen; Barba, Francisco J.; Castagnini, Juan Manuel; Voća, Sandra (Frontiers in Nutrition, 2022)
Nettle is a highly valued medicinal plant that is still largely neglected, both in terms of nutrition and use for pharmacological purposes. Tinctures, i.e., alcoholic extracts, are becoming increasingly popular nettle product, mainly because they allow better availability of phytochemicals and their stability over a longer period of time. The production of alcoholic extracts is a chemically demanding process that is still usually carried out using conventional techniques, which have numerous drawbacks. The use of green technologies such as ultrasound-assisted extraction (UAE), which is characterized by high efficiency of phytochemical extraction, shorter treatment time, and a much lower environmental footprint, is a possible solution. Therefore, the aim of this study was to determine the influence of the extraction method, conventional and ultrasound (by varying two ultrasound equipment systems), time and ethanol concentration on the extraction of specialized metabolites from nettle powder. Ultrasonic extraction using a probe system significantly contributed to increase the ascorbic acid yield, polyphenolic compounds, and antioxidant capacity of nettle extracts compared to conventional extraction. In addition, when a probe system was used during UAE, significantly less time was required for isolation of individual specialized metabolites compared to ultrasonic extraction in the bath. Ethanol concentration (50% and 80% v/v) also proved to be an important factor in the efficiency of extraction of specialized metabolites, with 80% ethanol being more effective for the isolation of ascorbic acid and pigment compounds (chlorophyll and carotenoids), while 50% v/v for the extraction of polyphenolic compounds. It can be concluded that extraction with the ultrasonic probe system is much more efficient in obtaining higher yields of specialized metabolites from nettle powder in a shorter time (average process duration 5-10 min) both compared to UAE in bath and classical extraction. However, optimization of the key factors of time, solvent type, and ultrasonic power is necessary to maintain the nutritional quality of the nettle extract in order to obtain a final product with a high specialized metabolites content, antioxidant capacity, and functional value.